Thermal oxygen coupling effects on multiple-layer degradation behaviors and full-field crack evolutions of 3D5d braided composites. (1st March 2023) - Long, Jing; Xu, Feng; Wu, Yuanyuan; Sun, Baozhong; Gu, Bohong
Abstract: Mechanical behaviors of thermo-oxidative aged 3D braided composites are affected by matrix degradation and crack evolution. Here we report multiple-layer degradation behaviors, spatial crack propagations and mechanical reduction mechanisms of three-dimensional five-directional (3D5d) braided composites under thermal oxygen coupling environment with dynamic thermomechanical analysis, Fourier transform infrared spectroscopy and X-ray micro-computed tomography. Ageing behaviors of samples in pure thermal environment were analyzed for comparison. Storage modulus of thermo-oxidative aged resins in rubbery state increases and a new tanδ peak appears, while these phenomena disappear after continuous removal of the oxidized layer. Oxidized molecular chains and re-crosslinking reactions occur on the near-surfaces of the thermo-oxidative aged resins. The cracks in the thermo-oxidative aged composites initiate and propagate faster than those in the thermal aged composites. Yarn arrangements affect the crack growth rates. The synergistic effect of oxygen and crack continuously reduces the mechanical properties of the 3D5d braided composites. Graphical abstract: Image 1